2009
DOI: 10.1002/da.20625
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric disorders among disaster bereaved: an interview study of individuals directly or not directly exposed to the 2004 tsunami

Abstract: The dual burden of direct trauma and loss can inflict a complex set of long-term reactions and mental health problems in bereaved individuals. The relationship between PGD and impaired functioning actualizes the incorporation of PGD in future diagnostic manuals of psychiatric disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 41 publications
7
42
1
2
Order By: Relevance
“…The estimated prevalence of CG was over 70%, much higher than documented prevalence of CG among the general population, which ranges from 2.5% to 25% (Kersting et al, 2011;Mizuno et al, 2012;Newson et al, 2011). It was also higher than findings in other post-disaster studies with rates between 37% and 45% (Johannesson et al, , 2009(Johannesson et al, , , 2011Kristensen et al, 2009;Neria et al, 2007;Shear et al, 2006). This is comparable only to one study conducted among 400 earthquake survivors in Iran, in which 76% of respondents were screened positive for CG (Ghaffari-Nejad et al, 2007).…”
Section: Discussionsupporting
confidence: 53%
“…The estimated prevalence of CG was over 70%, much higher than documented prevalence of CG among the general population, which ranges from 2.5% to 25% (Kersting et al, 2011;Mizuno et al, 2012;Newson et al, 2011). It was also higher than findings in other post-disaster studies with rates between 37% and 45% (Johannesson et al, , 2009(Johannesson et al, , , 2011Kristensen et al, 2009;Neria et al, 2007;Shear et al, 2006). This is comparable only to one study conducted among 400 earthquake survivors in Iran, in which 76% of respondents were screened positive for CG (Ghaffari-Nejad et al, 2007).…”
Section: Discussionsupporting
confidence: 53%
“…For example, using face-to-face structured clinical interviews, Kristensen et al (2009) reported that the prevalence rates of PTSD and depression among the directly exposed bereaved individuals two years after the 2004 tsunami disaster were 34.4% and 25% respectively. Kuo et al (2003) investigated the prevalence of PTSD and major depression among 120 bereaved survivors aged 12 to 84 years old two months after a severe earthquake in Taiwan and reported that the prevalence rates of PTSD and depression were 37% and 16% respectively.…”
Section: Discussionmentioning
confidence: 98%
“…In a study that involved survivors of loved ones lost in the September 11th attack, for example, approximately half of the bereaved participants who met criteria for CG did not meet criteria for any other category of psychopathology (Bonanno, Neria, et al, 2007). A recent study of Norwegians who lost first-degree family relations to the 2004 tsunami in Southeast Asia also confirmed the independence of CG reactions (Kristensen, Weisaeth, & Heir, 2009). Among those who lost family in the tsunami but were not directly exposed to the disaster (i.e., not in Asia at the time of the disaster), a small proportion (14.3%) developed CG.…”
Section: Prolonged and Traumatic Griefmentioning
confidence: 97%